House Prices, Housing Development Costs, and the Supply of New Single-Family Housing in German Counties and Cities - Oliver Lerbs (European Regional Science Association (ERSA), 2012)
This paper employs panel data on 413 counties and cities over 2004-2009 to investigate the local supply of new single-family housing in Germany. Construction activity in local housing markets (measured by new housing permits related to the local housing stock) is modeled as a function of local home prices and new housing development costs, with the latter including local costs related to construction and local costs of vacant land. The results suggest the permit rate in a location to be positively linked to higher local home price levels and recent increases in development costs, while higher levels of replacement costs dampen construction activity. The average price elasticity of new single-family home permits is considerably less than one, supporting recently published estimates based on national time-series data.
Keywords: 330